Implementasi Metode Simple Additive Weighting dalam Penentuan Guru untuk diusulkan Sertifikasi - Mahulae, Saut; Limbong, Tonni (MEANS (Media Informasi Analisa dan Sistem), 2019)
Teacher certification is a government effort in improving teacher quality by increasing teacher welfare, so that it will improve the quality of learning and the quality of education in a sustainable manner. The implementation of teacher certification is carried out by a process and several stages. The Simple Additive Weighting (SAW) method is a decision making technique by carrying out the weighted sum of each performance rating on each alternative of all attributes and requiring the decision matrix normalization process. This method is one method that can carry out multiple criteria assessments and in detail uses a comprehensive thinking framework and hierarchical process considerations which then calculates the weight for each criterion in determining the effectiveness of teacher certification submission in accordance with the quota.